Integrating Arabic Language Learning And Islamic Religious Education For Religious Character Formation - Ma'arif, A. Samsul; Rosikh, Fahrur (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2025)
This study examines the integration of Arabic language learning and Islamic Religious Education (IRE) in developing students’ religious character at MTs Hidayatul Mubtadi’in Malang. The integration aims to harmonize linguistic competence with the cultivation of Islamic moral values, forming a comprehensive educational model that aligns cognitive and affective domains. Using a qualitative descriptive approach with a case study design, data were gathered through classroom observations, interviews with teachers and students, and analysis of curricular documents. The results show that Arabic language instruction when contextualized with Qur’anic verses, prophetic traditions, and Islamic terminologies strengthens students’ understanding of religious ethics, discipline, and devotion. Teachers integrate linguistic content with moral instruction, fostering both language proficiency and spiritual awareness. This integration produces a holistic learning atmosphere that contributes to students’ spiritual formation and reinforces Islamic character education within the school environment.